Lectotypification of the name Justicia latiflora (Acanthaceae) - Tang, Huimin; Deng, Yunfei (Phytotaxa, 2016)
Justicia latiflora Hemsl. in Forbes & Hemsley (1890: 245) is a species endemic to China occurring in Chongqing, Guangxi, Guizhou, Hubei, Hunan and Yunnan (Hu 2002, Hu et al. 2011). Later, it was transferred to Mananthes Bremekamp (1948: 59) as M. latiflora (Hemsl.) C.Y.Wu & C.C. Hu in Hu (2002: 295). Mananthes is one of the genera separated from Justicia Linnaeus (1753: 15) by Bremekamp to accommodate those Asian species having terminal spikes and it now is treated as a synonym of Justicia (Scotland & Vollesen 2000, Hu et al. 2011). This species differs from differ from those Chinese species formerly included in Mananthes in its bracts being purplish towards the apex and longer than the calyces, with corollas ca. 2 cm long. Three collections (Henry 3412, 3412A, 3412B) were cited from K in the protologue. Since no holotype was indicated they all are syntypes according to Art. 9.5 (ICN, McNeill et al. 2012). According to Art. 9.12, the lectotype must be chosen from those syntypes in first place. Comparing the three syntypes at K with the original description, we found that all are a match and candidates for serving as a lectotype. Since Henry 3412 (K000884035) is the only specimen with open corollas, a feature described in the protologue, it is here selected as the lectotype.